Diferensiasi Fasakh, Khulu', dan Pembatalan Perkawinan dalam Fikih Mazhab dan Hukum Positif Indonesia - Zamzam Alfathoni Fillah; Muhammad Amar Adly; Heri Firmansyah (Ahlana: Jurnal Hukum dan Hukum Keluarga Islam, 2026)
This study seeks to examine, in a thorough manner, how the institutions of fasakh and marriage annulment operate when viewed through both Islamic jurisprudence and Indonesia’s positive law. Its central concern lies in the various grounds that justify fasakh, namely concealed physical defects, deception (tadlis), the disappearance of a spouse (mafqud), and sexual incapacity. Beyond that, the article traces the differing positions held by the four principal schools of jurisprudence (madzhab) concerning the juridical placement of fasakh, khulu’, and talak, while also reviewing how annulment is applied under Law Number 1 of 1974 together with the Compilation of Islamic Law (KHI). Methodologically, the work adopts a juridical-normative design carried out through library research. Findings reveal that fasakh and annulment alike operate as protective mechanisms intended to spare the wronged party from harm (mudharat). What distinguishes the two is the moment at which the defect emerges: annulment rests on flaws that taint the contract from its inception, whereas fasakh responds to circumstances that surface, or only become known, once the contract has been concluded. Within the Indonesian framework, annulment additionally safeguards children’s legal standing, treating them as legitimate even after their parents’ marriage has been set aside.